Adaptive Strategies of Enterprises in the Digital Environment - Zinchenko Olha A. (PH "INZHEK", 2021)
The article is aimed at substantiating the basics of adaptive control in the digital environment. The author puts forward and verifies a thesis on the necessity to develop adaptive strategic management amid the digital transformation of business on the basis of agile principles, which allow the most complete implementation of the customer-oriented approach. The author defines the adaptive strategy in the digital environment as a model of the company's adaptation to the digitalization of its interaction with customers, partners, competitors and other contact audiences. It has been suggested and proven that adaptive strategies are competitive in nature. Based on this hypothesis, adaptive strategies are systematized by the degree of their relevance in the digital environment. Strategies of cost optimization, differentiation, and focusing with reference to business digitalization are considered. The adaptive toolkit of these strategies is expanded by using more flexible methods and approaches. It is proved that the strategy of cost optimization is implemented thanks to such tools as business automation models, virtual product chains, combining real and virtual content of production processes (Building Information Model, blockchain technologies), and smart working model. A company can effectively differentiate its products and services by the digitalization of the existing products and services and the creation of new ones, convergence of consumer expectations based on SMAC (Social, Mobility, Analytics, Cloud) technologies, and through the omnichannel service of different customer groups. It is established that thanks to digital marketing and such technologies as authentic interaction, content marketing, social media marketing, performance branding, and affiliate marketing a company can strengthen its position in a certain market segment (or niche) and implement a customer-oriented approach. Risk management in the design of adaptive strategies in the digital environment can be seen as a prospect for further research.